Exemplary Leadership Qualities of Mathematics Teacher Leaders - Asamoah, Daniel; Abdullah, Nor Azura; Shahrill, Masitah; Laidin, Dalilah Farzana Haji; Ismail, Nur Fatin Haji; Abu Bakar, Najibah Pg; Shahrum, Mohamad Bahzi Al Barakat; Emran, Afiqah Bari’ah Haji; Abas, Nur Basmirah Haji (MASI Mandiri Edukasi, 2023)
In theorizing teacher leadership, little is known about the leadership qualities teachers are likely to learn or model within their community of practice. This descriptive qualitative study examined 12 graduate teacher candidates to describe the exemplary leadership qualities of mathematics teacher leaders. After thematic analysis, two categories of exemplary leadership qualities of mathematics teacher leaders were revealed: the leadership qualities they exhibit for students to imitate and the qualities they model from significant others in their community of practice. We conclude that exemplary leadership qualities are a function of role modeling and social learning. Implications for teacher leadership in mathematics education are discussed further in this paper.